Public costs and private benefits: the governance of energy efficiency in India. Issue 1 (2nd January 2019) - Mathur, Ajay
ABSTRACT: India has demonstrated that it is possible to reduce energy demand and increase the energy efficiency of its buildings, particularly for air-conditioning appliances. Given the rapid and large expected increase in India's building stock over the next 20 or more years, the opportunity exists to make significant increases in overall energy efficiency and reduce energy demand through the application of its Energy Conservation Building Code that influences the design, construction and operation of buildings. However, the responsibility for this code resides with local authorities (urban local bodies) that currently lack sufficient incentive to implement and enforce it. To overcome this impediment, it is argued here that important benefits can be captured by local authorities to implement energy-conservation measures: increased revenues from taxes, improved attractiveness to business and citizens, and the introduction of automation to reduce transaction costs in the building-approval process. Large parts of the country's property (real estate) are yet to be built, providing a valuable opportunity to transition to low-energy and climate-friendly solutions in India's rapidly growing building stock.